Pneumoscrotum with extensive subcutaneous emphysema in traumatic perineal injury: A case report - Tariq Siddiqui (444882) (2023)
Key Clinical Message We present a rare case of pneumoscrotum with subsequent subcutaneous emphysema in penetrating perineal injury with a tangential wound. It is important to diagnose the underlying disease and treat the cause. An examination under anesthesia is crucial for the diagnosis and management of the set of injuries. Pneumoscrotum with subcutaneous emphysema in traumatic perineal injuries is an alarming sign and may indicate life-threatening intraabdominal injuries or necrotizing fasciitis. We reported a case of pneumoscrotum and extensive subcutaneous emphysema of the abdomen and chest 2 days after admission. Pneumoscrotum was not seen on the initial Computerized tomographic scan. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.7932